Hubungan Durasi Bermain Gitar Dengan Risiko Carpal Tunnel Syndrome - Fahrurrozi Fiqi, Sanjaya; , Dwi Kurniawati, SSt. Ft., M.Kes; , Totok Budi Santoso, S.Fis., MPH (2016)
Background : For some people, playing guitar is pleasure thing, but to be a professional guitar player is needed a long time to expert technique play guitar correctly . the Long time playing guitar with can make the wrist to pain. Objective of Research : The objective is to know association duration playing guitar with tunnel carpal syndrome incident. Benefit of Research : To outlook of its information for Physiotherapy especially about the risk of Carpal Tunnel Syndrome for guitar player. Method of Research : The kind of research this is research quantitative with cross sectional approach. Sample are 42 guitar players in Surakarta. Instrument research use questionnaire measurement of carpal tunnel syndrome use phalen's test, tinel's sign test and pressure test. The collected data then test by using chi square test with significance 0.05. Result of Research : The results that 84,6 % ( 22 respondents ) who play guitar more than 2 hours a day experienced carpal tunnel syndrome. Statistic test results p = 0,000 ( p < 0.05 with OR = 12.1. Conclusion : Tthere is an association duration playing guitar with tunnel carpal syndrome incident. OR = 12.1 it means respondents who play guitar with duration more than two hours per day have risk 12 times more have risk carpal tunnel syndrome than respondent who play guitar less than two hours per day. Keyword : duration play guitar, Carpal Tunnel Syndrome